2010
DOI: 10.1021/bi100070r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Imatinib and Sorafenib Binding to p38α Compared with c-Abl and b-Raf Provides Structural Insights for Understanding the Selectivity of Inhibitors Targeting the DFG-Out Form of Protein Kinases

Abstract: Protein kinases c-Abl, b-Raf, and p38alpha are recognized as important targets for therapeutic intervention. c-Abl and b-Raf are major targets of marketed oncology drugs Imatinib (Gleevec) and Sorafenib (Nexavar), respectively, and BIRB-796 is a p38alpha inhibitor that reached Phase II clinical trials. A shared feature of these drugs is the fact that they bind to the DFG-out forms of their kinase targets. Although the discovery of this class of kinase inhibitors has increased the level of emphasis on the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 33 publications
(49 reference statements)
8
59
0
Order By: Relevance
“…We have recently published that p38 MAPK is induced by SN-38 and is responsible for the development of resistance to and that the use of p38 inhibitor can enhance the cytotoxic activity of SN-38 (9). Interestingly, we have found that sorafenib can inhibit the p38 activation mediated by irinotecan in vivo, confirming its inhibitory effect shown by Namboodiri and Grossi, respectively, in vitro and in cellulo (39,40). Therefore, sorafenib, by inhibiting the MAPK p38 pathway make the cells more sensitive to irinotecan.…”
Section: Discussionsupporting
confidence: 80%
“…We have recently published that p38 MAPK is induced by SN-38 and is responsible for the development of resistance to and that the use of p38 inhibitor can enhance the cytotoxic activity of SN-38 (9). Interestingly, we have found that sorafenib can inhibit the p38 activation mediated by irinotecan in vivo, confirming its inhibitory effect shown by Namboodiri and Grossi, respectively, in vitro and in cellulo (39,40). Therefore, sorafenib, by inhibiting the MAPK p38 pathway make the cells more sensitive to irinotecan.…”
Section: Discussionsupporting
confidence: 80%
“…The total standard binding free energies of Gleevec, ΔG (°) , accounting for the thermodynamic contributions associated with the conformational change of the DFG-flip in apo kinase (ΔG in→out ) and the ligand-binding free energy to the DFG-out conformation, are −9.4 kcal/mol and −1.4 kcal/mol for Abl and c-Src, respectively. The measured inhibitory potency of the drug for unphosphorylated Abl and c-Src is 0.013 μM and 31.1 μM, respectively, corresponding to a standard binding affinity of −10.8 kcal/mol and −6.2 kcal/mol, respectively (7,20). The poorer agreement for c-Src may be due to the fact that 13 residues from the A-loop, unresolved in the X-ray structure, were modeled from the inactive conformation.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been shown to target the DFG-out conformational state of p38α and to affect p38α kinase activity in vitro. 13,14 Sorafenib induces apoptosis by downregulating Mcl-1 in several cell lines and xenografted tumors, including HT-29 and HCT-116 CRC cells. 13,15,16 It has been approved for clinical use by the FDA in hepatocellular carcinoma (HCC) and renal cell carcinoma (RCC), but failed to prove efficacy in CRC Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…1) of BRAF and p38α. 13,14 Notwithstanding, clinical trials failed to demonstrate a beneficial effect for sorafenib in CRC patients.…”
Section: Discussionmentioning
confidence: 99%